Ways to improve tax control - Karminska-Bielobrova, Marina (Європейський університет, 2010)
Tax control finds its manifestation in the relationship between taxpayers (corporate and individuals) and state regulatory bodies.
Keywords: tax control; taxpayers; Ukraine